A descriptive survey of the significance of place attachment in the bedroom spaces of selected adolescents - Fraginal, Nikolette Flores
The study investigated the importance of the concept of place attachment and its significance in the residential bedroom spaces of selected adolescents. The researcher identified the physical and emotional factors that influence the concept of place attachment and provided further understanding on how this concept creates a significant role in the bedroom spaces of young adults. In this study, the researcher adopted multi-method approach as its research design. Purposive sampling was applied wherein the researcher selected five (5) adolescents aged eighteen (18) to twenty (20) years old from middle class families residing in the city proper of San Pablo City, Laguna. An interview guide, observation sheet and photo documentation were the tools used for data gathering during the observation and interview sessions with each respondent. After the researcher had gathered the sufficient data from her respondents, she proceeded in interpreting, tabulating and analyzing it using content analysis to determine the factors which influence the significance of place attachment. Based from the results of the data which were analyzed, here are seven physical factors which are: size of bedroom, personal style, layout and organization, ambiance, comfortable furniture, lighting and presence of media. The three emotional factors are: sense of personal identity and belongingness, the sense of ownership and territoriality and time spent. These factors influence the significance of the concept of place attachment in the bedroom spaces of the respondents. Also, it suggests that this concept is important and should be considered when it comes to designing the bedrooms for adolescents.